Upskilling Digital Competencies: A Case of Urban Poor Community in a Malaysian Residential Apartment - Omar, Muhamad Khalil; Dahalan, Noor Azura; Sharkawi, Sharizan; Abdullah, Dayang Nailul Munna Abg; Yusoff, Yusri Hazrol (Advances in Social Sciences Research Journal, 2024)
The coronavirus (COVID-19) pandemic disproportionately affects most employment, especially among the B40 community who are mostly low-skilled and earn a low income. On the other hand, in the current world of the Fourth Industrial Revolution (IR 4.0), everybody is required to have a strong digital competency to survive on a very competitive edge. Therefore, this research aims to understand the current level of digital competencies among the B40 community so that certain intervention mechanisms can be planned for the improvement of such needs. Additionally, a web-based one-stop platform called ‘SMARTCOM’ is to be introduced to the studied B40 communities to upskill them through personal training and engagement. This customized online platform would be a centralised communication channel including community members’ business information, job offerings, and income opportunities which shall be co-created with the committee members of the participating B40 communities. Consequently, a smart B40 community then be realised as its committees are empowered to manage their community digitally as well as its members are competent in utilising and optimising information technology sustainably. This study hence shall rapidly solve the income and job loss problems through socio-technological innovations thus enabling an on-demand and shared economy.